(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was aimed at in vitro antileishmanial screening of ten plants used in the traditional medicine in India. MTT method was used to evaluate the cell death after application of 100, 250, 350 and 500 ?g/mL of the methanolic extracts followed by incubation for 24 hours at 25°C. Methanolic leaf extracts of Acorus calamus, Alstonia scholaris and Berberis aristata showed significant antileishmanial activity at a concentration of 500 µg/ml. In order to identify the antileishmanial compounds present in the active extracts of the screened plants, an LC-MS analysis of the tested extracts was carried out. The active extracts revealed the presence of some natural products with known antileishmanial activity along with other compounds. The present study suggests that the active plant extracts may be processed to isolate the compounds that may further be screened for their antileishmanial potential.